Diurnal Circadian Variation in Photosynthesis in Dracaena Sanderiana Under Contrasting Temperature and Light - Jayasooriya L.S.H; Wijethunga W.M.U.D; Kumarihami H.M.P.C; Beneragama C.K (Indonesian Journal of Applied Research (IJAR), 2022)
Dracaena sanderiana is prominent and in-demand cut foliage in the global ornamental industry. This study was conducted to examine the stress responses of Dracaena sanderiana under contrasting temperature and light conditions by using chlorophyll fluorescence (ChlF) transient analysis technique. D. sanderiana cuttings were held in distilled water and subjected to two different light levels, i.e., 22,500±2,000 lux and 750±200 lux allowing two distinct temperature levels. The chlorophyll fluorescence data were collected through OJIP analysis using a portable fluorometer (FluorPen, FP 110). The measurements were recorded four times a day (9 am, 12 pm, 3 pm, and 6 pm) and the data were collected continuously for four days commencing from the first day of treatment application. The major parameters derived from the OJIP analysis, including specific energy fluxes per reaction center (ABS/RC, TR/RC, ET/RC, and DI/RC), flux ratios (maximum quantum yield of primary photochemistry-φPo, electron transport efficiency -ψo, and quantum yield of electron transport –φEo and maximum quantum yield of non-photochemical de-excitation- φDo), and performance index (PI) were recorded. ChlF data showed a clear unimodal diurnal variation in plant performances of D. sanderiana at 22,500±2,000 lux. The circadian variation was reported for all measured ChlF parameters except the ψo, TR/RC, and ET/RC. Based on these circadian variations of ChlF, it can be concluded that D. sanderiana displays a facultative CAM pathway as an adaptation to the stressed conditions.